2014
DOI: 10.22270/jddt.v4i3.829
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Tuber Part of the Traditional Medicinal Climber, Solena Amplexicaulis (Lam.) Gandhi. Against Certain Human

Abstract: The present study was made to evaluate the in vitro antimicrobial activity minimum inhibitory concentration of Solena amplexicaulis tuber extracts [hexane, benzene, chloroform, methanol and water] against 15 bacterial and 9 fungal species and to determine the minimum inhibitory concentration (MIC) for its methanolic extract against the human pathogens. In vitro antimicrobial activity was determined by using agar disc diffusion technique and MIC was determined by using broth dilution method. The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
1
4
0
5
Order By: Relevance
“…Even though the extracts were not as strong Fe 2+ chelators as EDTA, the investigated extract demonstrated notable chelating properties. Ferrous ion chelating activity of SAET was close to the results of Karthika et al [17]. Metal chelating capacity was significant as they reduced the concentration of catalyzing transition metal in lipid peroxidation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Even though the extracts were not as strong Fe 2+ chelators as EDTA, the investigated extract demonstrated notable chelating properties. Ferrous ion chelating activity of SAET was close to the results of Karthika et al [17]. Metal chelating capacity was significant as they reduced the concentration of catalyzing transition metal in lipid peroxidation.…”
Section: Discussionsupporting
confidence: 84%
“…This situation forced the researchers to search for new anti-microbial substance from various sources including medicinal plant [24]. Karthika and Paulsamy [17] reported that S. Amplexicaulis extracts of leaf and stem exhibited antibacterial and anti-fungal activity. The findings revealed that medicinal plant Solena amplexicaulis can play a vital role in combating fungal resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on use value, information consensus factor and fidelity level, Venkatachalapathi et al [11] reported that it is one among the five most important species in the treatment of inflammation and wound healing in Nilgiris of Western Ghats being prescribed by the Irula tribal community. In addition to this, it is known from the literature that the tubers are astringent, appetizer, carminative, cardiotonic, digestive, diuretic, expectorant, invigorating, purgative, stimulant, sour and thermogenic [12] .Our early laboratory data also recorded several therapeutic properties as antimicrobial [13] and antioxidant activities [14] and phytochemical constituents [15,16] for this species. Terpenoids, the characteristic feature of the family, Cucurbitaceae [17,18] are attributed to various pharmacological claims including antiinflammatory, anticancer, antimalarial, antiviral and antibacterial activities [19] .…”
mentioning
confidence: 75%
“…Untuk pemisahan metabolit sekunder yang ada di ekstrak daun gedi, ekstrak ditotolkam secara manual menggunakan pipa kapiler pada pelat silika gel GF254 dengan ukuran 10x5 cm, tebal 3 mm. Pelat yang telah ditotoli sampel dimasukkan ke dalam bejana yang sudah berisi fase gerak sesuai dengan metode Karthika et al, (2014)…”
Section: Uji Profil Kromatografi Lapis Tipis (Klt)unclassified